The prophylactic effects of naringin on steroid-induced early-stage osteonecrosis in rats: a preliminary study: The prophylactic effects of naringin on osteonecrosis - Zhuang, Jian; Wang, Jin; Zhang, Bingping; Chai, Dongpo; Zuo, Zhenbo (Cellular and Molecular Biology, 2023)
The excessive steroid may cause dyslipidaemia and oxidative insult during femoral head osteonecrosis, inducing bone loss and impairment of the intraosseous blood system. In contrast, bio-flavanone naringin has shown antioxidant, antiresorptive and lipid-lowering bioactivities. The present research is an effort to explore the anti-ON potential of naringin in vivo and in vitro. After a 6-week treatment, the femora were dissected for histological examination following bone mineral density assay by X-ray absorptiometry. Blood samples were examined for coagulation, oxidative stress, lipid transportation and endothelial injury. Marrow samples were cultured and assayed for adipogenic and osteogenic alterations by ALP activity, mineralization, RT-qPCR and western blot analysis. The results showed that naringin exerted a dose-dependent effect on reducing ON incidence, with inhibition of osteoporosis, oxidative stress and dyslipidaemia. The mechanism included the suppression of PPARγ2 for adipogenesis of bone marrow stem cells (BMSCs) and the prevention of oxidative stress in endothelium injury. Naringin may restore steroid-impaired osteogenesis by enhancing the mRNA and protein expression of osteogenic markers in a dose-ascending manner and new bone formation can be found in naringin groups. Taken together, our findings showed that naringin may serve as a prophylactic agent and selective PPARγ modulator for the early-stage ON.